ANALISIS PESAN DAKWAH MODERASI DALAM NOVEL KIDUNG RINDU DI TAPAL BATAS KARYA AGUK IRAWAN MN. - Rukayah, Siti; Qadaruddin, Muhammad; Haramain, Muhammad (LPPM IAIN Parepare, 2020)
The development of da'wah in the digital era is inseparable from the probelmatika of society as a target for da'wah and so many media are used as a means of da'wah. One of the means used by many preachers to deliver their da'wah material is through written media and literacy such as novels. The novel is one of the alternative dawah for delivering dawah material to the target of preaching or mad'u, many stories in the novel are promoted as messages of propaganda in the form of film media. This article has a very positive purpose in understanding the contents of da'wah what are the meanings in a story that have elements of nationalism and da'wah by using descriptive qualitative methods, then linking them to interpretations of the Qur'an. The results of this research are first the theme of da?wah moderation  raised in this novel about Garuda in my chest, in the da?wah moderation scheme the presence of dissatisfaction, sadness, sadness of life in his country but they eat in other countries, semantic messages of moderation means tolerance and  help each other, and belief in God Almighty.